ISOLATION AND IDENTIFICATION OF CORYNEBACTRIUM DIPHTHERIA FROM PATIENTS IN MOSUL PROVINCE - Enas Sami Mahmood (Web of Journals Publishing, 2023)
This thesis included isolating and diagnosing Corynobacterium by examining smears taken from the pseudohymenoptera in the pharynx, which is formed during the disease and the most important type of disease for humans in Corynebactrium diphtheria, which is positive and variable and may appear negative as a characteristic that is completely persistent and examined microscopically and then diagnosed using approved diagnostic methods Which comes in the forefront of the diagnostic biochemical tests, and the aim of this research is to identify the isolates that belong to the genera of these bacteria through the response of each isolate to a group of antibiotics used or not, and the severity of the sensitivity impairment. The antibiotics Chloramphenicol (5 mg) and Ampicllin (AP) were used and Erythromycin (5 mg), Streptomycin (25 mg), and Gentamycin (GM).
Keywords: Corynobacterium isolates, Antibiotics, Plant extract.